Liquidity requirements and payment delays - participant type dependent preferences - Christian Schulz (European Central Bank (ECB), 2011)
The paper presents an analysis of the trade-offs of participants of different type between payment delay and liquidity requirement on the basis of synthetically generated data. The generation of the synthetic transaction data set for a simple RTGS system is described and calibrated using real world parameters. The payment system is simulated for various liquidity levels and it is shown that participants of different size in terms of transaction volume and value will have different optimal liquidity requirements, as the payment delays they face for each liquidity level will be different. This is shown using indifference curves between payment delay and liquidity requirements.
Keywords: C15; C5; E58; L14; L41; L51; 330; competition; data generation; oversight; Payment system; Simulation